Experimental Identification of High-Reward Nectar Plants for the Monarch Butterfly (Danaus plexippus) - Veselovsky, Manon (Université d'Ottawa / University of Ottawa, 2025)
Monarch butterfly (Danaus plexippus) populations have significantly declined in the last 30 years. As a result, monarchs have been listed as 'Endangered' under Canada's Species at Risk Act, meaning conservation strategies must be developed and implemented to slow and reverse this decline. Monarchs migrate up to 5000 km from their breeding grounds in Canada to their wintering grounds in Central Mexico, with habitat loss and degradation occurring throughout their range. Consequently, restoration work is needed to increase monarch success across the continent of North America. Current work in Canada is focused on restoring grassland habitats with Asclepias spp. (milkweed species), the monarch's larval host plant, and nectar plants. While nutrient concentrations in nectar vary between plant species, little is known about the effects of nectar quality from different plant species on the performance of adult monarchs. For the most effective use of limited conservation resources, work must be done to identify the most beneficial nectar plant species for monarchs. For the migratory generation which does not breed, the effects of nectar on body composition have never been studied. This generation undergoes several physiological changes to build and maintain large fat stores for this journey, indicating that fat is a key factor for migration success. Consequently, I conducted an experimental study evaluating monarch butterflies' body condition (wet mass, fat, lean mass, and water mass) when foraging on one of seven nectar plant species for seven days. I found that nectar plant species significantly affected monarch fat mass, lean mass, and overall wet mass. These results indicate a need to carefully choose plants for restoration, as these choices could have implications for migration success. This study represents the first experimental test of the effects of nectar plants on monarch butterfly body composition, providing an approach for future studies to evaluate nectar plants across the monarch's range.
Keywords: Monarch butterfly; Habitat restoration; Conservation; Floral nectar